Lessons learned from the Baltic countries' response to the first wave of COVID-19. Issue 5 (May 2022) - Webb, Erin; Winkelmann, Juliane; Scarpetti, Giada; Behmane, Daiga; Habicht, Triin; Kahur, Kristiina; Kasekamp, Kaija; Köhler, Kristina; Miščikienė, Laura; Misins, Janis; Reinap, Marge; Slapšinskaitė-Dackevičienė, Agnė; et al.
Highlights: Estonia, Latvia, and Lithuania had a precarious starting point entering the COVID-19 pandemic. The Baltic countries promptly declared a state of emergency, before 30 reported cases. While case numbers remained low, the countries built up infrastructure and capacities. The 'Baltic bubble' countries employed a highly centralized national response. Health workforce strengthening and service delivery flexibility would support resilience. Abstract: The Baltic countries of Estonia, Latvia, and Lithuania shared a similar response to the first wave of the COVID-19 pandemic. Using the information available on the COVID-19 Health System Response Monitor platform, this article analyzed measures taken to prevent transmission, ensure capacity, provide essential services, finance the health system, and coordinate their governance approaches. All three countries used a highly centralized approach and implemented restrictive measures relatively early, with a state of emergency declared with fewer than 30 reported cases in each country. Due to initially low COVID-19 incidence, the countries built up their capacities for testing, contact tracing, and infrastructure, without a major stress test to the health system throughout the spring and summer of 2020, yet issues with accessing routine health care services had already started manifesting themselves. The countries in the Baltic region entered the pandemic with a precarious starting point, particularly due to smaller operational budgets and health workforce shortages, which may have contributed to their escalated response aiming to prevent transmission during the first wave. Subsequent waves, however, were much more damaging. This article focuses on early responses to the pandemic in the Baltic states highlighting measures taken to prevent virus transmission in the face of major uncertainties.